2021
DOI: 10.1111/ocr.12469
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar cortical plate changes associated with incisor retraction and its influence on the limits of orthodontic tooth movement

Abstract: Objective The extent to which the modelling behaviour of the anterior alveolus limits tooth movement remains unclear. Will the labial and lingual cortical plates model as incisors retract, or will they remain unchanged, therefore limiting the extent of possible tooth movement? Setting and Sample population. Pre‐ and post‐treatment lateral cephalometric radiographs of 29 bimaxillary protrusive patients of South Korean descent were examined. Treatment consisted of two premolar extractions in one or both arches w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Cancellous bone was found on the labial bone at the measured levels because the pure cortical bone was found on the labial plate. When pure cortical bone is detected on all labial plates, a light force should be applied to generate the desirable bone remodeling [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cancellous bone was found on the labial bone at the measured levels because the pure cortical bone was found on the labial plate. When pure cortical bone is detected on all labial plates, a light force should be applied to generate the desirable bone remodeling [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thongudomporn 24 and Elnagar et al 25 The authors found a significant posterior movement of the labial cortex and non-significant change in the palatal cortex following tooth retraction. 24,25 This study found no significant changes in the extraction group and the opposite result in the non-extraction group: the labial cortex did not significantly move, while the palatal cortex resorbed anteriorly.…”
Section: Discussionmentioning
confidence: 95%
“…[15][16][17]19,20 Recent systematic reviews and meta-analysis highlighted the low quality of currently available evidence published in English in extraction cases and the lack of non-extraction data. [21][22][23] A couple of studies investigated cortical positional changes using stable external structures 24,25 and found the labial cortex resorbing with incisor retraction while the palatal cortex remained unchanged. Using an extra-alveolar stable structure as reference would circumvent the potential errors found with the tooth axis, which changes as the incisor invariably tips when retracted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancellous bone was not found on the labial bone at the measured levels because pure cortical bone was found on the labial plate. When pure cortical bone is covered on all labial plates, light force should be used and always monitored [ 32 ].…”
Section: Discussionmentioning
confidence: 99%